Utilization of Waste to Minimize Environmental Pollution and Increase Income Through Creativity at SDN 5 Peninjoan - Laksmi P, Kadek Wulandari; Aris Widiana, Ngakan Putu (Jurnal Pengabdian Masyarakat, 2024)
Purpose: This research paper aims to address waste management issues in Peninjoan Village, Tembuku District, Bangli Regency, by educating elementary school students on effective practices. This initiative is significant for promoting environmental sustainability and community development. Method: The study uses an educational intervention at SDN 5 Peninjoan, collecting data through workshops and observational feedback. Qualitative analysis assesses students' understanding and their ability to transform waste into useful items. Practical Applications: The findings demonstrate practical applications, including improved community cleanliness, increased environmental awareness, and the development of marketable products, enhancing the income potential for families. Conclusion: Educating students on waste management fosters creativity and responsibility, allowing them to convert waste into valuable items. This research emphasizes the importance of integrating waste management education into school curricula to tackle environmental challenges effectively.